Inhibition effect of enteropeptidase on RANKL–RANK signalling by cleavage of RANK. Issue 18 (13th August 2013) - Zhao, Yunfeng; Jin, Mengmeng; Ma, Juan; Zhang, Shiqian; Li, Wei; Chen, Yuan; Zhou, Yingsheng; Tao, Hong; Liu, Yu; Wang, Lei; Han, Huamin; Niu, Ge; et al.
Abstract : EPcleaves mRANK bycleavage assay (View interaction) Abstract : There is a cleavage site on RANK for enzyme enteropeptidase. Enteropeptidase can block osteoclastogenesis by the cleavage of RANK. RANK can be used as a target to block RANKL–RANK signalling.